2016
DOI: 10.15412/j.bcn.03070309
|View full text |Cite
|
Sign up to set email alerts
|

Morphine-Induced Analgesic Tolerance Effect on Gene Expression of the NMDA Receptor Subunit 1 in Rat Striatum and Prefrontal Cortex

Abstract: Introduction:Morphine is a potent analgesic but its continual use results in analgesic tolerance. Mechanisms of this tolerance remain to be clarified. However, changes in the functions of μ-opioid and N-Methyl-D-aspartate (NMDA) receptors have been proposed in morphine tolerance. We examined changes in gene expression of the NMDA receptor subunit 1 (NR1) at mRNA levels in rat striatum and prefrontal cortex (PFC) after induction of morphine tolerance.Methods:Morphine (10 mg/kg, IP) was injected in male Wistar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…According to a previous study that represented in the molerat, opioid systems in the CNS may not be involved in the regulation of analgesia, but it can regulate several activity such as motor activity [23]. As well as, the other results of the hotplate test indicated that morphine (5 and 10 mg/kg) induced significant analgesia in naive rats but its analgesic effects in rats receiving 15 days injections of morphine (10 mg/kg) was reduced, showing tolerance to morphine analgesia [22]. The results of several studies have also indicated that NMDA receptor gene expression at mRNA level in rats tolerant to morphine is significantly increased in the striatum but decreased in the PFC.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…According to a previous study that represented in the molerat, opioid systems in the CNS may not be involved in the regulation of analgesia, but it can regulate several activity such as motor activity [23]. As well as, the other results of the hotplate test indicated that morphine (5 and 10 mg/kg) induced significant analgesia in naive rats but its analgesic effects in rats receiving 15 days injections of morphine (10 mg/kg) was reduced, showing tolerance to morphine analgesia [22]. The results of several studies have also indicated that NMDA receptor gene expression at mRNA level in rats tolerant to morphine is significantly increased in the striatum but decreased in the PFC.…”
Section: Discussionmentioning
confidence: 93%
“…According to the Figure -1B, two-way ANO-VA indicated that there is no significant interaction between tDCS and morphine in pain perception after 24 Although, post hoc analysis represented that the pre-test acute anodal left prefrontal tDCS does not significantly alter the analgesic effect in different doses on the day after the last morphine injection.…”
Section: Effects Of Subchronic Anodal Tdcs On the Morphine-induced Re...mentioning
confidence: 92%
See 1 more Smart Citation
“…Also, this proposes structural dependence by the neuromodulatory process to induce analgesia with potential relevance for patient stratification [ 26 ]. According to results of some studies, those indicated that long-term morphine administration creates tolerance to the antinociceptive effect of the opioid, as disclosed by a significant reduction in morphine-induced antinociceptive on day eight compared to day 1 of the injections [ 24 ]. Based on studies, several factors may describe the lack of objective impact of tDCS on morphine consumption and pain perception: the procedure of brain stimulation (tDCS/rTMS; repetitive Transcranial Magnetic Stimulation), possible interactions with anesthetic drugs, variations in subjects’ population, and the prior experience of pain and long-term utilization of antinociceptive drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of morphine on the spinal cord and brainstem neurons are mainly analgesic [ 102 ]. Long-term or repeated opioid exposure alters the expression levels of some genes in the spinal cord and brain regions, including the midbrain, striatum, hippocampus, and cortex [ 103 , 104 ]. Previous studies have shown that long-term exposure to opioids alters the expression of ncRNAs, which may be partly responsible for the sustained changes in gene expression after morphine treatment [ 105 ].…”
Section: Lncrna and Opioid Tolerancementioning
confidence: 99%